PENGEMBANGAN STRATEGI PEMASARAN BARU PADA PT. SIMEX PHARMACEUTICAL UNTUK MENINGKATKAN BRAND AWARENESS PRODUK VIPRO-G - Andry Kusnadi; Ryan Sastradihardja; Frida Findriani; Timotheus Lesmana Wanadjaja (Journal of Business Strategy and Execution, 2008)
Nowadays, along with development of technology and industry, pollution getting rises until healthy issue blossom out in Indonesia. A pharmacy company named PT. Simex Pharmaceutical tried to give solution by make a healthy product named Vipro-G with special quality for repairing damage or endotel vascular dysfunctional because of smoke pollution and also for society health. . Since 2006, PT. Simex launch Vipro-G in sachet’s which allocation for all society, not only for smoker. But then the image from Vipro-G is medicine for very active smoker, until PT. Simex Pharmaceutical has to decide right marketing strategy to displacement opinion which attribute to the Vipro-G and straight of their brand awareness. See the purpose from this thesis is one of graduated requirement to have Magister Management title and finishing Post Graduate Program at Universitas Bina Nusantara, also do to develop new marketing strategy for PT. Simex Pharmaceutical especially for Vipro-G marketing product. Method that we used for produce right marketing strategy to change PT. Simex position is by observation in marketing area with purpose to have information about current marketing strategy that used by PT. Simex, Affectivities Analyzing, and propose some new marketing strategy idea based on theory method of marketing strategy which equal for Vipro-G product. From several analyses that we have done, there are some marketing strategy and tactics from PT. Simex Pharmaceutical that still can re-new to achieve maximum result. Most of new marketing strategy that we propose is purpose to educated market intensively about Vipro-G and its function, because we found that most of society don’t know what is Vipro-G and its function.